2020
DOI: 10.1088/1755-1315/599/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Mini production suction dredge for small scale tin mining in Bangka Belitung Island Indonesia

Abstract: Mini Production Suction Dredge (MPSD) has been made for the people of Bangka Belitung Province Indonesia which is known as a cheap, safe and straightforward technology ship to mine tin sand from surface land under the sea level. This MPSD creates more safe production operation since the previous ships by using a traditional small boat for catching the fish. The main reason why this MPSD was created because there is no diving activity for an operator to drive the suction pipe flexibly under the sea which in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A total of 21 species of true mangrove and two associates (sensu Kitamura et al 1997) [54] were identified from various sampling sites on Bangka Island (Table 1). By considering the findings from previous studies on Bangka Island (Table 2), these data include approximately 70% of the species known to exist in Indonesia [60], and hence the island is representative at that level for the area with the second highest mangrove species richness worldwide (26)(27)(28)(29)(30)(31)(32)(33)(34)(35), as compiled by [2]. Notably, our findings indicate that there are no specific species (assemblages) restricted to either the southern or northern, the western or eastern parts of Bangka Island.…”
Section: Mangrove Species Composition and Distribution On Bangka Islandmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 21 species of true mangrove and two associates (sensu Kitamura et al 1997) [54] were identified from various sampling sites on Bangka Island (Table 1). By considering the findings from previous studies on Bangka Island (Table 2), these data include approximately 70% of the species known to exist in Indonesia [60], and hence the island is representative at that level for the area with the second highest mangrove species richness worldwide (26)(27)(28)(29)(30)(31)(32)(33)(34)(35), as compiled by [2]. Notably, our findings indicate that there are no specific species (assemblages) restricted to either the southern or northern, the western or eastern parts of Bangka Island.…”
Section: Mangrove Species Composition and Distribution On Bangka Islandmentioning
confidence: 99%
“…Open-pit mining is one of the tin extraction techniques utilised in the Bangka Islands [32]. This method involves the use of water guns and gravel pumps to extract tin sand from land surfaces or alluvial deposits [33]. Alluvial tin deposits, specifically with cassiterite (SnO 2 ), are exposed by removing vegetation and non-tin deposit overburden [34].…”
Section: Introductionmentioning
confidence: 99%